The Earth in God’s Economy: Creation, Salvation and Consummation in Ecological Perspective - Venter, Rian (Stellenbosch Theological Journal, 2016)
The Earth in God’s Economy: Creation, Salvation and Consummation in Ecological Perspective by Conradie, Ernst M Studies in Religion and the Environment, Vol. 10 2015, Lit Verlag GmbH & Co. KG Wien ISBN: 9783643906250